2011
DOI: 10.1002/glia.21241
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in expression of the astrocyte glutamate transporter, GLT1, worsens functional and histological outcomes following traumatic spinal cord injury

Abstract: The astrocyte glutamate transporter, GLT1, is responsible for the vast majority of glutamate uptake in the adult central nervous system (CNS), thereby regulating extracellular glutamate homeostasis and preventing excitotoxicity. Glutamate dysregulation plays a central role in outcome following traumatic spinal cord injury (SCI). To determine the role of GLT1 in secondary cell loss following SCI, mice heterozygous for the GLT1 astrocyte glutamate transporter (GLT1+/−) and wild-type mice received thoracic crush … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 36 publications
5
47
0
Order By: Relevance
“…We have consistently observed significant GLT1 downregulation in endogenous reactive astrocyte populations in both contusion and crush, as well as both cervical and thoracic, models of SCI (Lepore et al, 2011a; Lepore et al, 2011c; Li et al, 2014b; Putatunda et al, 2014; Watson et al, 2014). When we selectively increased GLT1 expression in these endogenous astrocytes in the unilateral cervical contusion model using an AAV8 vector, we paradoxically found that secondary degeneration of PhMNs and diaphragm denervation were worsened (Li et al, 2014b).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…We have consistently observed significant GLT1 downregulation in endogenous reactive astrocyte populations in both contusion and crush, as well as both cervical and thoracic, models of SCI (Lepore et al, 2011a; Lepore et al, 2011c; Li et al, 2014b; Putatunda et al, 2014; Watson et al, 2014). When we selectively increased GLT1 expression in these endogenous astrocytes in the unilateral cervical contusion model using an AAV8 vector, we paradoxically found that secondary degeneration of PhMNs and diaphragm denervation were worsened (Li et al, 2014b).…”
Section: Discussionmentioning
confidence: 63%
“…Transplantation also provides for long-term astrocyte integration and therapeutic replacement. For example, the lasting nature of dysregulation of extracellular glutamate homeostasis after SCI (Lepore et al, 2011a; Lepore et al, 2011c) calls for longer-term maintenance of therapeutic effects, both with respect to early cell loss occurring during secondary degeneration and outcomes of SCI associated with more persistent pathophysiology of glutamate signaling such as chronic neuropathic pain (Gwak et al, 2012; Hulsebosch, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Failure of long-term extrasynaptic glutamate clearance is suspected to be one major cause of secondary cell loss following SCI. Noteworthy, we and others demonstrated that astrocyte GLT1 was chronically lost at the injury epicenter following SCI but also downregulated in spinal cord regions distant from the lesion core [103][104][105][106] . Furthermore, experimental data showed that the newlygenerated astrocytes arising during the SCI repair phase lacked GLT1 expression, possibly compromising long-term astrocyte glutamate homeostasis [107] .…”
mentioning
confidence: 66%
“…Many studies have reported that changes in the distribution and the expression levels of GLAST and GLT-1 lead to excessive glutamate uptake, which is involved in brain injury and other neurological disorders (Coulter and Eid, 2012;Lepore et al, 2011). The JAK/STAT pathway has also been suggested to be involved in the modulation of glutamatergic neurotransmission (Raymond et al, 2011).…”
Section: Sps-induced Ptsd Increased the Glutamate Concentration In Thmentioning
confidence: 98%